Ocular lesions in gerbils (Meriones unguiculatus) infected with low larval burden of Toxocara canis: observations using indirect binocular ophthalmoscopy Lesões oculares em gerbils (Meriones unguiculatus) infectados com baixo número de larvas do Toxocara canis: observações com oftalmoscopia binocular indireta - Ledilma Inês Duarte Colodetti Zanandréa; Gabriela Mantovanelli Oliveira; Andressa Silva Abreu; Fausto Edmundo Lima Pereira (Revista da Sociedade Brasileira de Medicina Tropical, 2008)
To study the frequency of ocular lesions in 30 gerbils infected with 100 embryonated eggs of Toxocara canis, indirect binocular ophthalmoscopy was performed 3, 10, 17, 24, 31 and 38 days after infection. All the animals presented larvae in the tissues and 80% presented ocular lesions. Hemorrhagic foci in the choroid and retina were present in 92% of the animals with ocular lesions. Retinal exudative lesions, vitreous lesions, vasculitis and retinal detachment were less frequent. Mobile larvae or larval tracks were observed in four (13.3%) animals. Histological examination confirmed the ophthalmoscopic observations, showing that the lesions were focal and sparse. In one animal, there was a larva in the retina, without inflammatory reaction around it. The results demonstrated that gerbils presented frequent ocular lesions after infection with Toxocara canis, even when infected with a small number of embryonated eggs. The lesions observed were focal, consisting mainly of hemorrhages with signs of reabsorption or inflammation in different segments of eye, and differing from the granulomatous lesions described in ocular larva migrans in humans. Para verificar a freqüência de lesões oculares em 30 gerbils infectados com 100 ovos larvados de Toxocara canis foi realizada a oftalmoscopia binocular indireta nos dias 3, 10, 17, 24, 31 e 38 após a infecção.Todos os animais apresentavam larvas nos tecidos e 80% apresentavam lesões oculares, dos quais 92% tinham lesões hemorrágicas focais na coróide e na retina. Lesões exudativas da retina, lesões do vítreo, vasculite e descolamento da retina foram menos freqüentes. Larva móvel ou traços de larva em quatro (13,3%) animais. O estudo histológico confirmou as observações da oftalmoscopia, mostrando que as lesões eram focais e esparsas. Em um animal havia uma larva na retina, sem reação inflamatória em torno dela. Os resultados demonstraram que os gerbils apresentam freqüentes lesões oculares após infecção com o Toxocara canis mesmo quando infectados com pequeno número de ovos ...